Assessment of Eccentric-Concentric Exercises Applied in Different Resistances in Terms of Strength - Oktay Çakmakçı; Ali Tatlıcı (Selcuk University, 2022)
The purpose of this study was to examine the effects of eccentric-concentric exercises applied at different resistances on strength parameters. Thirty-five sedentary volunteers participating in the study were divided into 4 groups by the stratified randomization method according to their mean strength parameters. These groups were named as control group (CG) (age 21.00 ± 2.44 years, height 178.13 ± 6.83 cm, body weight 80.13 ± 12.14 kg), eccentric group (EG) (age 22.22 ± 2.99 year, height 178.22 ± 5.95 cm, body weight 71.22 ± 9.36 kg), con-eccentric group (CEG) (age 21.22 ± 2.86 year, height 177.22 ± 4.68 cm, body weight 71.89 ± 13.93 kg) and modified con-eccentric group (MCEG) (age 21.67 ± 2.59 year, height 177.00 ± 4.30 cm, body weight 75.22 ± 8.16 kg). During the 8-week training period, 4 sets of leg extension exercises with different loads were applied to the training groups 3 days a week. Isokinetic strength outputs were measured both concentrically and eccentrically at 60°s-1 ve 180°s-1 angular velocities with the Cybex device. SPSS 24 package program was used in the statistical analysis of the data. For normally distributed data, paired sample t-test was used in paired comparisons, and a one-way ANOVA test was used for comparison between three or more groups. Tukey and Dunnett's T3 (non-homogeneous) test was used among the post hoc tests. Wilcoxon test (paired comparisons) and Kruskal-Wallis test were used for nonparametric data. When the intragroup comparisons were examined before and after the training period, it was found that the isokinetic strength outputs of EG, CEG, and MCEG showed a significant increase in all contractions and angular velocities (p lt;0.05), but no parameters increased in CG (p gt;0.05). When the isokinetic pre-test strength parameters between the groups were compared, no significant difference was found (p gt;0.05). While only MCEG increased significantly in 180°s-1 concentric strength outputs, 60°s-1 and 180°s-1 eccentric strength output increased significantly in both MCEG and EG compared to CG (p lt;0.05). As a result, when the strength tests are considered, although the general strength development is seen mostly in MKEG, no statistically significant difference was found between training groups. It is recommended to determine the load in the eccentric phases of the exercises by the eccentric 1RM (repetition maximum), at least as a result of this research, to generate more strength development rates while applying strength training.